Clustering of Learning Media User Data During Covid-19 Pandemic Using K-Means Method Based on Multicultural Culture in Indonesia - Evi Fatimatur Rusydiyah; Hikmah Rossyta Virgiannada; Mujib Ridwan; Bayu Adhi Nugroho; Moh Rifqi Rahman (Journal of Innovation in Educational and Cultural Research, 2021)
Learning applied in Indonesia from elementary school to undergraduate level generally uses face-to-face or direct learning methods. However, after the Covid-19 disease outbreak, all methods change to online learning methods at all levels and cultures. This affects all aspects of learning such as comfort, understanding and learning outcomes. To find out the difference in the results using face-to-face methods and online methods, a study was carried out on classifying learning media users from elementary school to university level using the k-means method. This study aimed to determine the differences in learning outcomes between the semester before the Covid-19 pandemic and the semester during the Covid-19 pandemic which applies online learning. The results of grouping data on online learning media users showed that all levels of education were considered sufficiently ready to implement online learning. As well as cultural differences in Indonesia have not had an impact on the commitment of schools to implement online learning during the Covid-19 disease outbreak.